2022
DOI: 10.1088/1742-6596/2265/2/022086
|View full text |Cite
|
Sign up to set email alerts
|

Spatially distributed and simultaneous wind measurements with a fleet of small quadrotor UAS

Abstract: The understanding of micro-scale flow in the atmospheric boundary layer is one major challenge in wind energy research. Besides the broad possibilities of numerical simulations, experimental data are necessary for tests of the flow conditions within a wind farm under real conditions. In wind energy and atmospheric science, a variety of measurement devices exist for measuring the wind speed. We propose a measurement system that enables completely flexible simultaneous wind measurements using a fleet of multirot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The accuracy of the wind direction measurements is determined to 4.5 • . In Wetz and Wildmann (2022) we also found that the temporal resolution of wind measurement is limited to 2 Hz due to sensor noise which dominates in small scales. This is crucial at low turbulence conditions with low signal-to-noise ratio.…”
Section: Wind Algorithmmentioning
confidence: 75%
See 4 more Smart Citations
“…The accuracy of the wind direction measurements is determined to 4.5 • . In Wetz and Wildmann (2022) we also found that the temporal resolution of wind measurement is limited to 2 Hz due to sensor noise which dominates in small scales. This is crucial at low turbulence conditions with low signal-to-noise ratio.…”
Section: Wind Algorithmmentioning
confidence: 75%
“…We have previously shown that the calibration results for the mean wind vector and the velocity variance of the UAS measurements are in good agreement with the reference measurements using the calibration pattern close to the 99-m mast (Wetz and Wildmann 2022). The following analysis are based on the 'horizontal pattern' as illustrated in Assuming that eddies are transported with the mean advection velocity ū, the wavelengths are defined as…”
Section: Validation Of Turbulence Measurementsmentioning
confidence: 85%
See 3 more Smart Citations